Full-biodegradable polyester composite material and preparation method of thermal shrinkage film thereof

By using biodegradable materials such as starch, PBAT and PLA, the problem of difficult decomposition of polyethylene heat shrink film is solved, and high biodegradation rate and good mechanical properties under corroded composting conditions are achieved. Environmental protection standards.

CN119242003APending Publication Date: 2025-01-03LIAONING LINGGUAN NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411516116.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing polyethylene heat shrink film is difficult to decompose, resulting in environmental pollution, and it is necessary to develop a full biodegradable heat shrink film to solve this problem.

Method used

Using biodegradable materials such as starch, polyadipic acid-butylene terephthalate (PBAT) and polylactic acid (PLA), the fully biodegradable polyester composite materials are prepared through high-speed mixers and twin-screw extrusion mechanisms, and the A heat shrink film is prepared in a film blowing machine to adjust the heat shrinkage rate to meet the needs.

Benefits of technology

Under the conditions of decompost, the biodegradation rate of 91.22%, the products are carbon dioxide and water, which meets the GB/T 41010-2021 standard, and the heat-shrinkable film has good mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242003A_ABST
    Figure CN119242003A_ABST
Patent Text Reader

Abstract

The invention relates to a full-biodegradable polyester composite material and a heat shrink film thereof. Corn starch, PBAT and PLA are used as main raw materials, glycerin, water and polyethylene glycol-6000 are used as composite plasticizers, B225 is used as an antioxidant, and solid paraffin and oleamide are used as lubricants. The preparation method comprises the following steps: adding corn starch, glycerol, water, PEG-6000, B225, solid paraffin and oleamide into a high-speed mixer, stirring to obtain plasticized corn starch, adding PBAT and PLA into the high-speed mixer, mixing with the plasticized corn starch, stirring, discharging, putting into an extruder, extruding and granulating to obtain a full-biodegradable polyester composite material, and extruding and blowing to obtain the thermal shrinkage film. The polyester composite material prepared by the invention can be biodegraded under the condition of matured compost, the biodegradation rate is 91.22%, the relative biodegradation rate is 96.55%, and products are carbon dioxide and water and meet the GB / T 41010-2021 standard requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fully biodegradable packaging materials and discloses a preparation method of a fully biodegradable polyester composite material and a heat shrinkable film thereof. Background Art

[0002] Heat shrink film is a skin-fitting packaging material with good shrinkage and certain shrinkage stress, which is used to stabilize, cover and protect products. Polyethylene (PE) heat shrink film has the advantages of good flexibility, strong impact resistance, tear resistance, not easy to break, not afraid of moisture, large shrinkage rate, stable shape, etc., so it is widely used in the whole-piece packaging of products such as wine, cans, mineral water, various beverages, cloth, etc. However, polyethylene materials are difficult to decompose in the environment, causing serious pollution to land, oceans and water sources, so the research and development of fully biodegradable heat shrink film is of great significance to solving environmental pollution problems.

[0003] Polybutylene adipate-terephthalate (PBAT) is a completely biodegradable aliphatic-aromatic copolyester with high ductility and elongation at break. Its degradation is mainly achieved through enzymatic decomposition by bacteria, fungi or algae in the environment and non-enzymatic action by thermal degradation and chemical hydrolysis, which eventually produces carbon dioxide and water. Polylactic acid (PLA) is formed by dehydration condensation of lactic acid molecules and has good biocompatibility and biodegradability. Its degradation products are carbon dioxide and water. Starch is a natural polymer that is widely found in plants such as corn, wheat, rice, potato, and cassava. It has the advantages of wide sources, low price, complete biodegradability, and short regeneration cycle. It is one of the most promising biodegradable materials. Summary of the invention

[0004] In order to solve the environmental pollution problem caused by heat shrinkable films made of non-degradable polyethylene materials, the object of the present invention is to provide a method for preparing a fully biodegradable polyester composite material and a heat shrinkable film thereof. The present invention first places additives such as starch, plasticizer, antioxidant and lubricant in a small high-speed mixer, controls a certain temperature, and stirs at high speed for a certain time to obtain plasticized starch. Polybutylene adipate-terephthalate (PBAT) and polylactic acid (PLA) of different masses are added to the high-speed mixer and continue to stir for a certain time to obtain a modified mixed material. The modified mixed material is placed in a small twin-screw extruder for melt blending, and extrusion granulation is performed to obtain a fully biodegradable polyester composite material. The obtained fully biodegradable polyester composite material is placed in a small film blowing machine for film blowing to obtain a heat shrinkable film. The heat shrinkage rate of the heat shrinkable film in the present invention can be adjusted by the ratio of the two biodegradable polyesters PBAT and PLA. The prepared polyester composite material can be biodegraded under mature composting conditions (test cycle 140d), with a biodegradation rate of 91.22% and a relative biodegradation rate of 96.55%. The products are carbon dioxide and water, which meets the requirements of GB / T 41010-2021 standard.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a fully biodegradable polyester composite material and a heat shrinkable film thereof, wherein the fully biodegradable polyester composite material and the heat shrinkable film thereof are made of biodegradable starch, polybutylene adipate-terephthalate (PBAT) and polylactic acid (PLA) as main raw materials, and plasticizers, antioxidants and lubricants as auxiliary agents.

[0006] A method for preparing a fully biodegradable polyester composite material and a heat shrinkable film thereof comprises the following steps:

[0007] (1) Preparation of plasticized starch: Weigh starch, plasticizer, antioxidant and lubricant, place in a small high-speed mixer, control the temperature to a certain level, and stir at high speed for a certain period of time to obtain plasticized starch.

[0008] Preferably, the starch is corn starch, the plasticizer is glycerol, water and polyethylene glycol-6000, the antioxidant is B225, and the lubricant is solid paraffin and oleamide.

[0009] Preferably, the mass ratio of the starch, glycerol, water and polyethylene glycol-6000 is 20:2:1:1.

[0010] Preferably, the mass ratio of the starch to B225, solid paraffin and oleamide is 100:0.3:0.6:1.25.

[0011] Preferably, the material temperature is 95°C.

[0012] Preferably, the stirring speed is 10 Hz.

[0013] Preferably, the stirring time is 55 min.

[0014] (2) Preparation of modified mixture: Weigh PBAT and PLA into a high-speed mixer, mix with plasticized starch, control the temperature, continue stirring for a certain period of time, and then discharge the material to obtain a modified mixture.

[0015] Preferably, the mass ratio of plasticized starch to PBAT and PLA is 2:5-7:1-3.

[0016] Preferably, the material temperature is 105°C.

[0017] Preferably, the stirring speed is 15 Hz.

[0018] Preferably, the stirring time is 25 min.

[0019] (3) Preparation of fully biodegradable polyester composite materials: The modified mixed material is placed in a small twin-screw extruder, the temperature of each zone is controlled to melt blend, and extrusion granulation is performed to obtain a fully biodegradable polyester composite material.

[0020] Preferably, the temperature of each zone of the small twin-screw extruder is: 145°C in zone one, 150°C in zone two, 150°C in zone three, 155°C in zone four, and 155°C in zone five.

[0021] (4) Preparation of fully biodegradable heat shrinkable film: placing the fully biodegradable polyester composite material in a small film blowing machine, controlling the temperature of each zone, and blowing the film to obtain a fully biodegradable heat shrinkable film.

[0022] Preferably, the temperature of each zone of the film blowing machine is: 150° C. in zone 1, 155° C. in zone 2, 155° C. in zone 3, 160° C. in zone 4, and 160° C. in zone 5, and the thickness of the heat shrinkable film is 0.045 mm.

[0023] Beneficial effects of the present invention:

[0024] The target product of the present invention is a fully biodegradable polyester composite material and a heat shrinkable film thereof. Its main raw materials, corn starch, PBAT and PLA, are biodegradable polymer materials, which are completely biodegraded under mature composting conditions, and the final products are carbon dioxide and water. The heat shrinkage rate of the heat shrinkable film of the present invention can be adjusted by the ratio of PBAT and PLA. In addition, the PBAT resin used has a high elongation at break, and PLA has a strong mechanical strength, which can ensure the mechanical properties of the heat shrinkable film products. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 These are actual photos of a fully biodegradable polyester composite material 1 (A) and a heat shrinkable film 1 (B).

[0026] Figure 2These are actual photos of a fully biodegradable polyester composite material 2 (A) and a heat shrinkable film 2 (B).

[0027] Figure 3 These are actual photos of the fully biodegradable polyester composite material 3 (A) and the heat shrinkable film 3 (B).

[0028] Figure 4 It is a graph showing the change of carbon dioxide production of the fully biodegradable polyester composite material 3 over time.

[0029] Figure 5 It is a graph showing the biodegradability of the fully biodegradable polyester composite material 3 over time. DETAILED DESCRIPTION

[0030] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0031] Example 1 A method for preparing a fully biodegradable polyester composite material 1 and a heat shrinkable film 1 thereof

[0032] 1. Preparation of plasticized starch

[0033] Weigh 2.0 kg corn starch, 0.2 kg glycerol, 0.1 kg water, 0.1 kg polyethylene glycol-6000 and 0.005 kg B225, 0.01 kg solid paraffin and 0.02 kg oleamide and put them in a small high-speed mixer. Control the material temperature at 95° C., the stirring speed at 10 Hz, and stir for 55 min to obtain plasticized starch.

[0034] 2. Preparation of modified mixture

[0035] Weigh 6.5 kg PBAT and 1.5 kg PLA into a small high-speed mixer, mix with plasticized starch, control the material temperature at 105° C., stir at 15 Hz, stir for 25 min, and obtain a modified mixture.

[0036] 3. Preparation of fully biodegradable polyester composite materials 1

[0037] The modified mixed material was placed in a small twin-screw extruder, and the temperatures of zone 1, zone 2, zone 3, zone 4, zone 4 and zone 5 were controlled at 145°C, 150°C, 15 ... Figure 1 (A) shown.

[0038] 4. Make fully biodegradable heat shrink film 1

[0039] The fully biodegradable polyester composite material 1 was placed in a small film blowing machine, and the temperatures of zone 1, zone 2, zone 3, zone 4, zone 4 and zone 5 were controlled at 155°C, 155°C, 160°C, and 160°C, respectively, to obtain a fully biodegradable heat shrinkable film 1. The photo of the heat shrinkable film 1 is shown in FIG. Figure 1 (B) Density: 1.252g / cm 3 , film thickness: 0.045mm, shrinkage rate: 12% in the horizontal direction and 69% in the vertical direction.

[0040] Example 2 A method for preparing a fully biodegradable polyester composite material 2 and a heat shrinkable film 2 thereof

[0041] 1. Preparation of plasticized starch

[0042] Weigh 2.0 kg corn starch, 0.2 kg glycerol, 0.1 kg water, 0.1 kg polyethylene glycol-6000 and 0.005 kg B225, 0.01 kg solid paraffin and 0.02 kg oleamide and put them in a small high-speed mixer. Control the material temperature at 95° C., the stirring speed at 10 Hz, and stir for 55 min to obtain plasticized starch.

[0043] 2. Preparation of modified mixture

[0044] Weigh 5.5 kg PBAT and 2.5 kg PLA into a small high-speed mixer, mix with plasticized starch, control the material temperature at 100° C., stir at 15 Hz, stir for 25 min, and obtain a modified mixture.

[0045] 3. Preparation of fully biodegradable polyester composite materials 2

[0046] The modified mixed material was placed in a small twin-screw extruder, and the temperatures of zone 1, zone 2, zone 3, zone 4, zone 4 and zone 5 were controlled at 145°C, 150°C, 15 ... Figure 2 (A) shown.

[0047] 4. Make fully biodegradable heat shrink film 2

[0048] The fully biodegradable polyester composite material 2 was placed in a small film blowing machine, and the temperatures of zone 1, zone 2, zone 3, zone 4, zone 4 and zone 5 were controlled at 155°C, 155°C, 160°C, and 160°C, respectively, to obtain a fully biodegradable heat shrinkable film 2. The photo of the heat shrinkable film 2 is shown in FIG. Figure 2 (B) Density: 1.276g / cm 3 , film thickness: 0.045mm, shrinkage rate: 16% in the horizontal direction and 72% in the vertical direction.

[0049] Example 3 A method for preparing a fully biodegradable polyester composite material 3 and a heat shrinkable film 3 thereof

[0050] 1. Preparation of plasticized starch

[0051] Weigh 2.0 kg corn starch, 0.2 kg glycerol, 0.1 kg water, 0.1 kg polyethylene glycol-6000 and 0.005 kg B225, 0.01 kg solid paraffin and 0.02 kg oleamide and put them in a small high-speed mixer. Control the material temperature at 95° C., the stirring speed at 10 Hz, and stir for 55 min to obtain plasticized starch.

[0052] 2. Preparation of modified mixture

[0053] Weigh 4.5 kg PBAT and 3.5 kg PLA into a small high-speed mixer, mix with plasticized starch, control the material temperature at 100° C., stir at 15 Hz, stir for 25 min, and obtain a modified mixture.

[0054] 3. Preparation of fully biodegradable polyester composite materials

[0055] The modified mixed material was placed in a small twin-screw extruder, and the temperatures of zone 1, zone 2, zone 3, zone 4, zone 4 and zone 5 were controlled at 145°C, 150°C, 15 ... Figure 3 (A) shown.

[0056] 4. Make fully biodegradable heat shrink film 3

[0057] The fully biodegradable polyester composite material 3 was placed in a small film blowing machine, and the temperatures of zone 1, zone 2, zone 3, zone 4, zone 4 and zone 5 were controlled at 155°C, 155°C, 160°C, and 160°C, respectively, to obtain a fully biodegradable heat shrinkable film 3. The photo of the heat shrinkable film 3 is shown in FIG. Figure 3 (B) As shown, density: 1.312g / cm 3 , film thickness: 0.045mm, shrinkage rate: 20% in the horizontal direction and 80% in the vertical direction.

[0058] The biodegradability of the fully biodegradable polyester composite material 3 was tested by the Jilin Provincial Product Quality Supervision and Inspection Institute. The test method was GB / T 19277.1-2011 "Determination of the ultimate aerobic biodegradability of materials under controlled composting conditions by measuring the released carbon dioxide method Part 1: General method". The reference material in the experimental data was provided by the Jilin Provincial Product Quality Supervision and Inspection Institute. The results are as follows Figure 4 , Figure 5 As shown in Table 1, it can be biodegraded under mature composting conditions (test period 140d), with a biodegradation rate of 91.22%, a relative biodegradation rate of 96.55%, and the products are carbon dioxide and water, which meets the requirements of GB / T 41010-2021 standard.

[0059] Table 1 Biodegradation rate data of fully biodegradable polyester composite material 3 and reference material

[0060] Related information Fully biodegradable polyester composite material 3 Reference Materials Inoculum Mature compost Mature compost <![CDATA[Total volatile solid ratio mat v / d > 97.29% 99.98% 45-day biodegradability 69.45% 76.43% Ultimate biodegradability 91.22% 94.48% Test cycle 140 days 140 days

[0061] It can be seen from the above three embodiments that as the PLA component in the polyester increases, the transverse and longitudinal shrinkage rates of the heat shrinkable film increase. Therefore, the shrinkage rate of the heat shrinkable film can be adjusted by changing the PLA content in the polyester.

[0062] It can be understood that the above specific description of the present invention is only used to illustrate the present invention and is not limited to the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effects. As long as the use requirements are met, they are within the protection scope of the present invention.

Claims

1. A fully biodegradable polyester composite material, characterized in that: The fully biodegradable polyester composite material mainly comprises biodegradable starch, polyester, plasticizer, antioxidant and lubricant.

2. The method for preparing a fully biodegradable polyester composite material according to claim 1, characterized in that: The following steps are involved: (1) Weighing starch, plasticizer, antioxidant and lubricant, placing them in a high-speed mixer, controlling the temperature to a certain level, and stirring at a high speed for a certain period of time to obtain plasticized starch; (2) adding the biodegradable polyester to the plasticized starch, controlling the temperature to continue high-speed stirring for a certain period of time, and discharging the material to obtain a modified mixed material; (3) placing the modified mixed material in a small twin-screw extruder, controlling the temperature of each zone for melt blending, extruding and granulating, and air-cooling and pelletizing to obtain a fully biodegradable polyester composite material.

3. The method for preparing a fully biodegradable polyester composite material according to claim 2, characterized in that: The starch is one of corn starch, potato starch and tapioca starch.

4. The method for preparing a fully biodegradable polyester composite material according to claim 3, characterized in that: The polyester is two or more of polybutylene adipate-terephthalate PBAT, polybutylene succinate PBS, polycaprolactone PCL and PLA.

5. The method for preparing a fully biodegradable polyester composite material according to claim 4, characterized in that: The plasticizer is at least three of glycerol, water, polyethylene glycol-6000, propylene glycol and urea; the antioxidant is one of antioxidant B225, antioxidant 168 and antioxidant B215; the lubricant is two of solid paraffin, polyethylene wax, calcium stearate and oleamide.

6. The method for preparing a fully biodegradable polyester composite material according to claim 5, characterized in that: The mass ratio of the starch to glycerol, water to polyethylene glycol-6000 is 40:2-12:1-6:1-6, the mass ratio of the starch to the antioxidant B225, solid paraffin and oleic acid amide is 100:0.1-0.5:0.5-1.0:1.0-1.5, the material temperature of the high-speed mixer is controlled to be 90-100°C, the rotation speed is 5-20Hz, and the stirring time is 30-60min.

7. The method for preparing a fully biodegradable polyester composite material according to claim 6, characterized in that: The mass ratio of plasticized starch, PBAT and PLA is 2:3-10:1-5, the material temperature of the high-speed mixer is controlled to be 100-110°C, the rotation speed is 10-20Hz, and the stirring time is 10-30min.

8. The method for preparing a fully biodegradable polyester composite material according to claim 7, characterized in that: In step (3), the temperatures of the zones of the twin-screw extruder are: 145-150° C. for zone 1, 150-155° C. for zone 2, 150-155° C. for zone 3, 155-160° C. for zone 4, and 155-160° C. for zone 5.

9. A fully biodegradable heat shrinkable film, characterized in that: The fully biodegradable polyester composite material according to claim 1 is placed in a film blowing machine, and the temperature of each zone is controlled to blow the film to obtain a fully biodegradable heat shrinkable film.

10. A fully biodegradable heat shrinkable film according to claim 9, characterized in that: The temperatures of each zone of the blow molding machine are: zone 1 145-150°C, zone 2 150-155°C, zone 3 150-155°C, zone 4 155-160°C, zone 5 155-160°C, and the thickness of the heat shrinkable film is 0.04-0.045mm.

Citation Information

Cited By

  • High-toughness PLA shrink film and preparation method thereof

    CN121133246A

  • High-tenacity pla shrink film and method of making same

    CN121133246B

  • Biodegradable thermal shrinkage film with three-layer structure and preparation method thereof

    CN121608500A